Guardians of the valley : Chickasaws in colonial South Carolina and Georgia - Cashin, Edward J., 1927-2007 (University of South Carolina Press, 2009)
This is the first comprehensive history of the Lower Chickasaws in the Savannah River Valley. Edward J. Cashin, the preeminent historian of colonial Georgia history, offers an account of the Lower Chickasaws, who settled on the Savannah River near Augusta in the early eighteenth century and remained an integral part of the region until the American Revolution. Fierce allies to the English settlers, the Chickasaws served as trading partners, loyal protectors, and diplomatic representatives to other southeastern tribes. In the absence of their benevolence, the English settlements would not have developed as rapidly or securely in the Savannah River Valley. Aided by his unique access to the modern Chickasaw Nation, Cashin has woven together details on the eastern Chickasaws from diverse source materials to create this cohesive narrative set against the shifting backdrop of the Southern frontier. The Chickasaws offered primary allegiance to South Carolina and Georgia at different times in their history but always served as a link in ongoing trade between Charleston and the Chickasaw homeland in what is now Mississippi. By recounting the political, social, and military interactions between the native peoples and settlers, Cashin introduces readers to a colorful cast of Chickasaw leaders, including Squirrel King, the Doctor, and Mingo Stoby, each an important component to a story that has until now gone untold. - Publisher.